The Interconnectivity of Heutagogy and Education 4.0 in Higher Online Education - Kim, Jeanne (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2022)
Industry 4.0 advancements in technology are creating a dynamic and fast changing world that affects how we live and work. Educators need to rethink existing teaching approaches to better prepare learners for future careers that Industry 4.0 will create. The World Economic Forum defined a new education model, called Education 4.0, which contains eight major changes to redefine learning in the new economy. Heutagogy, or self-determined learning, is an approach that promotes critical thinking, social-emotional skills, and life-long learning. These skills are necessary for Education 4.0. The purpose of this paper is to recommend the principles of heutagogy as an effective teaching and learning approach to meet the needs of Education 4.0. The approach of the study examines existing literature on Education 4.0 and heutagogy. A conceptual model that interconnects heutagogy to the four learning principles of Education 4.0 will be offered as a key finding to answer the research question: How does heutagogy in higher online education meet the needs of Education 4.0? The paper provides a base for further research and discussion into how heutagogy and other approaches can support the needs of Education 4.0 to prepare learners for a changing world.